2021
DOI: 10.1097/scs.0000000000007623
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Sinus Fractures: A Review on Etiology and Management Emphasizing Minimally Invasive and Endoscopic Techniques

Abstract: It is a safe and reliable flap, and the blood supply is unaffected in patients with prior neck dissection. In comparison with other locoregional flaps, the upper trapezius myocutaneous flap fulfills all aesthetic and functional criteria for secondary cervicofacial soft tissue reconstruction in ''frozen neck.'' REFERENCES 1. Krijgh DD, Mureau MA. Reconstructive options in patients with late complications after surgery and radiotherapy for head and neck cancer: remember the deltopectoral flap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The treatment approach is generally selected according to the extent of sinus wall displacement and associated injuries, such as nasofrontal duct involvement or CSF leakage. 1,18,34,35 Observation is believed to be sufficient for nondisplaced or minimally displaced fractures of the anterior table in which the integrity of the nasofrontal duct is preserved. 22 Patients with a more severe displacement of the anterior table should undergo a careful clinical examination to determine whether surgical intervention with sinus preservation or sinus obliteration would be required to correct the esthetic deformity and any possible lesions to the drainage system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The treatment approach is generally selected according to the extent of sinus wall displacement and associated injuries, such as nasofrontal duct involvement or CSF leakage. 1,18,34,35 Observation is believed to be sufficient for nondisplaced or minimally displaced fractures of the anterior table in which the integrity of the nasofrontal duct is preserved. 22 Patients with a more severe displacement of the anterior table should undergo a careful clinical examination to determine whether surgical intervention with sinus preservation or sinus obliteration would be required to correct the esthetic deformity and any possible lesions to the drainage system.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study are similar to those of several authors who recommended a nonoperative approach for managing frontal sinus fracture in most patients, whereas surgical reconstruction, obliteration, or cranialization were reserved for just a few cases with severe complications. 7,10,[16][17][18][19] Schultz et al 7 found that patients with posterior table fractures were more likely to undergo cranialization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The frontal sinus develops after birth at approximately 2 years of age, reaching adult size after puberty 12 with direct visualization radiographically possible after 5 to 7 years of age. 13 The frontal sinus can be divided into three sections and includes (1) a thick anterior table, (2) a thin posterior table, and (3) a nasofrontal outflow tract (NFOT) that drains the sinus into the middle meatus of the nose (►Fig. 1).…”
Section: Anatomy and Development Of The Frontal Sinusmentioning
confidence: 99%